Applying The Circular Model Of Some To Digital Public Relations: Instagram And Brand Image Construction In Taman Budaya Yogyakarta - Irgiawan Aditya Rangga; Iva Fikrani Deslia (INJECT (Interdisciplinary Journal of Communication), 2025)
This research aims to analyze the digital public relations strategy through Instagram social media in shaping the brand image of Taman Budaya Yogyakarta (TBY) as “The Window of Yogyakarta”. The method employed is a descriptive, qualitative approach, utilizing case study techniques through in-depth interviews, observation, and documentation. The results showed that the management of the @tamanbudayayogya Instagram account follows the principles of The Circular Model of SOME, which consists of Share, Optimize, Manage, and Engage. Taman Budaya Yogyakarta utilizes Instagram as a strategic communication medium to disseminate cultural content, build audience engagement, and form emotional connections with the public through two-way interaction, visual content, and collaboration with various external parties. This approach has also proven effective in building a positive image of cultural institutions amidst the challenges of the digital era, making Instagram a key instrument in strengthening Taman Budaya Yogyakarta's identity as Yogyakarta's cultural window.